Spatial Thinking Analysis of Geographic Students Based on Lesson Study for Learning Community (Lslc) in Geographic Learning - Rahmanelli, Rahmanelli; Prarikeslan, Widya (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Spatial thinking in geography learning is very important to explain phenomena, find meaning, answers, and solutions about shape, size, orientation, location, direction, objects in certain spaces on the earth's surface. Therefore, geography students must be able to solve problems in their environment through spatial thinking. "Lesson Study for Learning Community" is considered one of the right approach to solve the problem. The research was conducted at the Department of Geography, FIS UNP in the January-June 2018 semester. The subjects of the study were geography students registered in 2016. The data collected through observation by 6 observers. Learning scenarios follow the steps of Lesson Study; "Plan", "Do" and "See". The data were analyzed by using data reduction, display and data verification techniques. The result of study show that students' spatial thinking skills based on "Lesson Study for Learning Community" can solve the problem of geography learning, both in asking, answering, discussing, and expressing opinions. Learning is more directed, fun, and collaborating between students, model lecturer, and observers.